Functional block in the initiation and maintenance of common flutter: detailed electrophysiological study and electro-anatomical mapping - Arnaud, Marine; Sacristan, Benjamin; Hocini, Meleze; Jais, Pierre; Haissaguerre, Michel; Duchateau, Josselin (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThe precise pathophysiology of common atrial flutter remains imperfectly known. The mechanisms of arrhythmia initiation and the role of areas of slow conducting myocardium and functional block are still debated topics.MethodsWe conducted a detailed electrophysiological study of a patient to illustrate and refine these concepts. Prior to CTI ablation, electrophysiological study and electro-anatomical mapping were performed, focusing on initiation and maintenance mechanisms of the arrhythmia.ResultsThe initiation of common atrial flutter takes place on the septal aspect of the cavo-tricuspid isthmus where functional unidirectional conduction block occurs. The direction of activation is therefore frequently counter-clockwise, and the arrhythmia stabilizes around the vena cavas and sinus venosus/crista terminalis region. No conduction slowing is present.ConclusionsCommon atrial flutter initiates when functional unidirectional conduction block occurs on the septal cavotricuspid isthmus. Its rotation is limited by anatomical and functional boundaries.